Comparing the effect of two coating methods of Tetragonula laeviceps propolis water extraction on physical quality and shelf life of eggs kept in room temperature - I., Kinasih; U., Julita; Y., Suryani; T., Cahyanto; E.M., Khoirunnisa; R.E., Putra (Penerbit Universiti Kebangsaan Malaysia, 2020)
Studies show that in the tropical region, like Indonesia, eggs have a low shelf life, ranging from 10 to 14 days when kept at room temperature. The application of natural coating material, such as propolis, could improve the shelf life of eggs. However, due to the high cost of the material, it is necessary to find more efficient application methods. In this study, propolis extraction using aquadest as solvent was applied, by brushing and spraying, to 180 fresh eggs of local chicken (Gallus sp.) aged 24 hours with another 180 eggs, without propolis coating, designed as control. All eggs were kept in room temperature for 35 days and changes on the albumen index, yolk index, and height of air sacs were measured every 7 days. This study showed that the different application methods did not significantly affect the value of the albumen index and yolk index for each observation time, but haugh unit and height of the air cell. However, the result indicated that the application of propolis by spraying maintained egg quality for a longer time than brushing and the average shelf life of eggs sold at the local market.